2015
DOI: 10.1073/pnas.1424563112
|View full text |Cite
|
Sign up to set email alerts
|

Anti-vascular endothelial growth factor treatment normalizes tuberculosis granuloma vasculature and improves small molecule delivery

Abstract: Tuberculosis (TB) causes almost 2 million deaths annually, and an increasing number of patients are resistant to existing therapies. Patients who have TB require lengthy chemotherapy, possibly because of poor penetration of antibiotics into granulomas where the bacilli reside. Granulomas are morphologically similar to solid cancerous tumors in that they contain hypoxic microenvironments and can be highly fibrotic. Here, we show that TB-infected rabbits have impaired small molecule distribution into these disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
196
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(206 citation statements)
references
References 35 publications
5
196
1
1
Order By: Relevance
“…Various animal studies suggest that anti‐VEGF treatment, such as the widely prescribed anti‐VEGF antibody bevacizumab, can resolve vascular leakiness and improve outcome of TB (Datta et al, 2015; Oehlers et al, 2014; Oehlers et al, 2016). With the rising awareness that host‐directed therapy could be a valuable addition to antibiotics, VEGF seems to be an interesting target.…”
Section: Discussionmentioning
confidence: 99%
“…Various animal studies suggest that anti‐VEGF treatment, such as the widely prescribed anti‐VEGF antibody bevacizumab, can resolve vascular leakiness and improve outcome of TB (Datta et al, 2015; Oehlers et al, 2014; Oehlers et al, 2016). With the rising awareness that host‐directed therapy could be a valuable addition to antibiotics, VEGF seems to be an interesting target.…”
Section: Discussionmentioning
confidence: 99%
“…Datta et al [61] shown that TB-infected rabbits have impaired small molecule distribution into these disease sites due to a functionally abnormal vasculature, with a low-molecularweight tracer accumulating only in peripheral regions of granulomatous lesions. Granuloma-associated vessels are morphologically and spatially heterogeneous, with poor vessel pericyte coverage in both human and experimental rabbit TB granulomas.…”
Section: Granuloma Structurementioning
confidence: 99%
“…These nonreplicating bacteria can reenter the replicating state when hypoxia is relieved, as a granuloma shrinks. Reducing hypoxia in granulomas has been suggested as a strategy to resensitize bacteria to antibiotics (100). The dynamics between bacterial load, granuloma size, and bacterial growth clusters are also evident if we examine multiple granulomas at multiple time points between 200 and 1,000 dpi ( tuberculosis's ability to slow its growth, i.e., its ability to enter growth cluster 4 (but not its ability to accumulate lipid inclusions), leads to lower bacterial loads and higher sterilization rates (Fig.…”
Section: Resultsmentioning
confidence: 99%